2005
DOI: 10.2190/1yh2-51j5-tg3e-utfu
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Transliminality and Boundary Structure Subscales

Abstract: An opportunity sample of 98, mostly undergraduate [1], participants completed Thalbourne's Transliminality Scale (Form B) [2–3] plus three subscales from Hartmann's Boundary Structure Questionnaire [4] (sleep/wake/dream, unusual experiences, thoughts/feelings/moods) plus a psychic experiences scale which included some of Hartmann's items. The results support the hypothesis, and Houran et al.'s [5] findings, that there is a significant positive correlation between selected boundary structure subscales and a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…Individuals reporting EE and altered states of consciousness also show tendencies toward schizotypy (Pizzagalli et al, 2001), dissociation (Richards, 1991), transliminality (Sherwood and Milner, 2004–2005), hypersensibility (Thalbourne, 2000; Jawer, 2006), and “thin-boundariedness” (Hartmann, 1991). However, it is unknown what type of precise relationship a particular EE may have with particular beliefs and personality traits.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals reporting EE and altered states of consciousness also show tendencies toward schizotypy (Pizzagalli et al, 2001), dissociation (Richards, 1991), transliminality (Sherwood and Milner, 2004–2005), hypersensibility (Thalbourne, 2000; Jawer, 2006), and “thin-boundariedness” (Hartmann, 1991). However, it is unknown what type of precise relationship a particular EE may have with particular beliefs and personality traits.…”
Section: Introductionmentioning
confidence: 99%
“…As participants were recruited from two populations, a number of planned comparisons were conducted to assess sample differences. A significant difference in ASMR scores was observed across website of recruitment, t( 382 In examining the demographic differences of each sample, it was found that Facebook (Rawlings, 2002), RTS (Sherwood & Milner, 2004), PBCS (Miller, Murphy, & Buss, 1981). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Scale Means and Frequenciesmentioning
confidence: 99%
“…Sharing significant features with Hartmann's (1991) concept of mental boundaries, high levels of transliminality may represent a form of thin boundary between levels of consciousness (Sherwood & Milner, 2004) and the external environment (Thalbourne & Maltby, 2008). Comprising the words "trans" (cross) and "limen" (threshold; Sherwood & Milner, 2004), transliminality has been defined as the hypersensitivity toward (Thalbourne & Maltby, 2008), and tendency for psychological material to transcend the threshold of conscious awareness (Lange, Thalbourne, Houran, & Storm, 2000).…”
Section: Asmr and Transliminalitymentioning
confidence: 99%
See 2 more Smart Citations